A printed high gain UWB vivaldi antenna design using tapered corrugation and grating elements - Kumar Pandey G.; Kumar Meshram M. (My University, 2025)
A compact Vivaldi antenna is proposed with high gain over the ultrawideband (UWB) using novel combination of corrugation and grating elements. As it is very intricate to improve the radiation characteristics such as gain throughout the UWB using single technique, therefore, corrugation at the flares and grating elements in the area of tapered slot are used to improve gain over the UWB. Due to the corrugation, the gain and front-to-back ratio improved significantly over 3-8 GHz whereas the effect of grating elements is observed over 8 GHz. The antenna operates for 2.9 GHz to more than 12 GHz with S11<-10 dB and is designed on 0.8-mm thick low cost FR4 substrate (40 mm × 45 mm). The proposed antenna shows nearly stable unidirectional radiation patterns, peak realized gain more than 5 dBi, and front-to-back ratio better than 10 dB over the UWB. Furthermore, the time domain study of the antenna is carried out which shows good pulse handling capability with nearly flat group delay. © 2015 Wiley Periodicals, Inc.